Genetic Characterization of a Neurovirulent West Nile Virus Variant Associated with a Fatal Great Grey Owl Infection - Katarína Peňazziová; Ľuboš Korytár; Patrik Pastorek; Juraj Pistl; Diana Rusňáková; Tomáš Szemes; Viktória Čabanová; Martina Ličková; Kristína Boršová; Boris Klempa; Tomáš Csank (Viruses, 2021)
This study reports on a fatal case of a captive great grey owl infected with the West Nile virus (WNV) in the zoological garden Košice, eastern Slovakia (Central Europe). The tissue samples of the dead owl were used for virus isolation and genetic characterization. The novel isolate is genetically closer to Hungarian, Greek, and Bulgarian strains from the central/southern European clade of lineage 2 than to the strains previously isolated in Slovakia. Interestingly, it carries NS3-249P, a molecular virulence determinant associated with higher neurovirulence, which has not previously been observed in Slovakia. Subsequent serological investigation of the captive owls revealed additional seropositive animals, indicating local WNV transmission. Although no WNV-positive mosquitoes were found, the presence of the WNV principal vector Culex pipiens complex together with the described fatal case and further serological findings indicate an endemic focus of bird-neurovirulent WNV variant in the area.